Different immunological mechanisms govern protection from experimental stroke in young and older mice with recombinant TCR ligand therapy - Dotson, Abby L.; Zhu, Wenbin; Libal, Nicole; Alkayed, Nabil J.; Offner, Halina (Frontiers in Cellular Neuroscience, 2014)
Stroke is a leading cause of death and disability in the United States. The lack of clinical success in stroke therapies can be attributed, in part, to inadequate basic research on aging rodents. The current study demonstrates that recombinant TCR ligand therapy uses different immunological mechanisms to protect young and older mice from experimental stroke. In young mice, RTL1000 therapy inhibited splenocyte efflux while reducing frequency of T cells and macrophages in the spleen. Older mice treated with RTL1000 exhibited a significant reduction in inflammatory cells in the brain and inhibition of splenic atrophy. Our data suggest age specific differences in immune response to stroke that allow unique targeting of stroke immunotherapies.